Consumer Information-seeking for Social Products - Peter Schafer; Nina Overton (Communicare)
THIS study proposes that marketing communication can be approached within a socio-psycho logical framework, where market-related information is subject to both internal (cognitive) and external or social influences, specifically reference groups. The concept of Information-seeking within this framework implies that the consumer is actively involved in the interchange of market related Information, and that he actively seeks Information relevant to his goals in the purchase situation. A broad spectrum of literature on Information-seeking is systemized according to the nature and sources of information seeking. From this model, a number of propositions regarding the nature and sources of consumer information seeking for social products are formulated, which form the basis of the empirical investigation. While the findings of the study point to the pervasive influence of reference groups in Information-seeking and consumer behaviour, they also indicate that there is a clear distinction between direct, verbal reference group influence communicated by Informal personal sources and in direct, non-verbal reference group influence communicated by formal, non-personal sources. A number of implications for marketers and advertisers are suggested.